Antibacterial osteogenesis-promoting metal implant as well as preparation method and application thereof
By loading the MoS2 membrane on the surface of the titanium-based bone metal implant and modifying the exosomes to form an antibacterial composite membrane layer that promotes bone, the sterile loosening and bacterial infection problems in clinical applications of titanium-based implants are solved, and the antibacterial and bone-promoting effect of the implant is achieved.
Patent Information
- Application Number
- CN202510095713.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The existing titanium-based bone metal implants have problems of aseptic loosening and bacterial infection in clinical applications, and their surface bioinergies are poor, and their integration and antibacterial properties are insufficient.
By loading the MoS2 membrane on the surface of the titanium-based metal implant and modifying the exosomes on the MoS2 membrane, an antibacterial bone-promoting composite membrane layer is formed. MoS2 membranes have photocatalytic and photothermal effects, which can kill bacteria, while exosomes promote cell proliferation and bone repair.
The antibacterial effect on the surface of the implant is achieved and the bone binding performance is promoted, which reduces the risk of bacterial infection and sterile loosening, and improves the overall performance of the implant.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedicine and biomaterials, and in particular to an antibacterial bone-promoting metal implant and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Effective reconstruction of bone defects is a challenging problem in orthopedic surgery. Autologous bone transplantation and allogeneic bone transplantation are currently the most widely used methods for repairing bone defects. However, for autologous transplants, they are limited by the source of donors and do not match the defect site. The additional damage to the donor site and the frequent need for secondary surgery inhibit autologous bone transplantation; allogeneic and xenotransplantation have the risk of disease transmission and immune rejection, and also face problems such as high failure rate and poor mechanical stability. At the same time, the implantation of stem cells, such as bone marrow mesenchymal stem cells and adipose-derived stem cells, is also considered an alternative strategy. However, the implantation of stem cells also faces major challenges, including immune rejection, teratoma formation and undirected cell differentiation. Medical titanium and its alloys have been used to prepare hard tissue repair devices such as artificial joints, bone repair materials, and dental implants due to their good mechanical properties, chemical stability and biocompatibility. However, titanium and titanium alloys are bioinert materials with poor osteogenic properties and no antibacterial properties. In clinical practice, aseptic loosening and bacterial infection are important causes of implant failure in orthopedic implants. The biological inertness of the titanium-based implant surface makes it less integrated with the surrounding bone tissue, which can easily lead to aseptic loosening. Secondly, titanium and titanium alloy implants themselves lack antibacterial properties, and the surface is prone to bacterial adhesion and even biofilm formation, which can lead to implant-related infection problems. Solving the problems of aseptic loosening and bacterial infection is urgent. After the implantation surgery, cell adhesion-bone integration and bacterial adhesion-biofilm formation occur at the titanium alloy implant surface interface. It is urgent to develop effective implant surface modification strategies to alleviate the problem of premature implant failure. Therefore, it is of great practical significance to construct titanium-based implants that are both antibacterial and osteogenic. Summary of the invention
[0004] In order to overcome the above problems, the present invention provides an antibacterial bone-promoting metal implant and a preparation method and application thereof.
[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions: The first aspect of the present invention provides an antibacterial bone-promoting metal implant, which uses a metal implant as a substrate, the surface of the substrate is loaded with a MoS2 film, and the MoS2 film is modified with exosomes.
[0006] As an antibacterial material, MoS2 can produce photocatalytic and photothermal effects under external light stimulation, generate reactive oxygen and local high temperature to synergistically kill bacteria without causing damage to cell tissues. Under light-free conditions, the sharp edges of MoS2 nanosheets on the MoS2 film can penetrate or cut the bacterial cell membrane, causing leakage of cell contents and bacterial death. Exosomes are tiny vesicles with a lipid bilayer membrane structure with a diameter of about 30 to 150 nm that can be secreted by most cells in the body. They have the functions of promoting cell proliferation and differentiation, regulating immunity, etc.
[0007] In one or more embodiments, the metal implant comprises a titanium-based implant.
[0008] In one or more embodiments, the exosome source includes cells and / or body fluids; The cells include at least one of human, rat or mouse stem cells, macrophages, endothelial cells and epithelial cells.
[0009] The second aspect of the present invention provides a method for preparing the antibacterial bone-promoting metal implant according to the first aspect, comprising the following steps: (1) Roughening the surface of the metal implant; (2) dissolving sodium molybdate and thioacetamide in water to obtain a mixed solution, immersing the roughened metal implant in the mixed solution to carry out a hydrothermal reaction, and obtaining a metal implant with a surface-loaded MoS2 film after the reaction is completed; (3) immersing the metal implant with the MoS2 film loaded on the surface into a distearoylphosphatidylethanolamine-polyethylene glycol-lipoic acid solution containing dispersant nano-titanium dioxide, and irradiating with light to obtain a phospholipid polyethylene glycol-lipoic acid-modified MoS2 film; (4) dropping the exosomes onto the surface of the metal implant in step (3), and incubating to obtain an antibacterial bone-promoting metal implant.
[0010] In one or more embodiments, in step (1), the roughening treatment includes sandblasting and acid etching.
[0011] Preferably, during the sandblasting and acid etching treatment, the abrasive particles used include Al2O3.
[0012] Preferably, during the sandblasting and acid etching treatment, the size of the abrasive particles used is 150-250 μm, preferably 200 μm.
[0013] Preferably, during the sandblasting and acid etching treatment, the air flow velocity is 200-220 m / min, preferably 210 m / min; the nozzle distance is 14-18 cm, preferably 15 cm; the gas pressure is 0.8-1.0 bar, preferably 0.9 bar; and the sandblasting time is 25-35 s, preferably 30 s.
[0014] Preferably, during the sandblasting and acid etching treatment, the acid etching solution used is a hydrochloric acid solution.
[0015] In one or more embodiments, in step (2), the temperature of the hydrothermal reaction is 180-220° C., preferably 200° C.; the time of the hydrothermal reaction is 12-48 h, preferably 24 h.
[0016] In one or more embodiments, in step (2), the molar ratio of sodium molybdate to thioacetamide is (0.8-1.2):(3.5-5), preferably 1:4.
[0017] In one or more embodiments, in step (2), the concentration of sodium molybdate in water is 2-30 mM.
[0018] In one or more embodiments, in step (3), the concentration of the distearoyl phosphatidylethanolamine-polyethylene glycol-lipoic acid solution is 0.2-1 g / L, preferably 0.3 g / L.
[0019] In one or more embodiments, in step (3), the mass ratio of nano-titanium dioxide to distearoyl phosphatidylethanolamine-polyethylene glycol-lipoic acid is 1:1-1:20, preferably 1:10.
[0020] In one or more embodiments, in step (3), the concentration of nano-titanium dioxide is 0.8-1.2 g / L, preferably 1 g / L.
[0021] In one or more embodiments, in step (3), the light irradiation reaction time is 8 to 24 h, preferably 12 h.
[0022] In one or more embodiments, in step (4), the amount of exosomes added is 28-35 μL, preferably 30 μL; the concentration of the exosome solution is 10 7 ~10 11 / mL, preferably 10 10 Pieces / mL.
[0023] In one or more embodiments, in step (4), the incubation is carried out in a dark environment, and the incubation temperature is 3-5°C, preferably 4°C.
[0024] In one or more embodiments, in step (4), the incubation time is 12 to 36 h, preferably 24 h.
[0025] The third aspect of the present invention provides the use of the antibacterial osteopromoting metal implant in the preparation of orthopedic and / or dental metal implants.
[0026] The beneficial effects of the present invention are: (1) The present invention first sandblasts and acid-etches the titanium alloy to obtain a surface microstructure, then prepares a MoS2 film layer by hydrothermal reaction, and loads exosomes on the MoS2 film layer to obtain a composite film layer with both antibacterial and osteogenic properties. As an antibacterial material, MoS2 can produce photocatalytic and photothermal effects under external light stimulation, produce reactive oxygen and local high temperature to synergistically kill bacteria, and will not cause damage to cell tissues. The surface of molybdenum disulfide has a certain adsorption capacity, which can interfere with the normal metabolic process of bacterial cells by adsorbing some key substances on the surface of bacterial cells, thereby affecting the survival and reproduction of bacteria. Under light-free conditions, the sharp edges of MoS2 nanosheets on the MoS2 film can penetrate or cut the bacterial cell membrane, causing the cell contents to leak and the bacteria to die. Exosomes are a type of tiny vesicles with a lipid bilayer membrane structure with a diameter of about 30 to 150 nm that can be secreted by most cells in the body. They have the functions of promoting cell proliferation and differentiation, regulating immunity, etc.
[0027] (2) Exosomes are a type of liposomes. Their structure is more affected by the external environment than chemical drugs. The choice of temperature, pH, charge, and solvent type all have an important impact on the morphological structure of exosomes. Compared with the traditional strategy of loading drugs on metal substrates, loading exosomes is more difficult. At present, the strategies for loading exosomes mainly include hydrogel encapsulation, swelling adsorption, charge adsorption, etc., and the release of exosomes is mainly based on diffusion. Compared with the time required for tissue growth and healing, the release rate of exosomes is relatively fast and cannot be controlled later. Metal surfaces can generally adsorb a small amount of biomacromolecules through electrostatic effects, but this adsorption is more unstable. In order to solve the problem of loading and controllable release of exosomes on the MoS2 membrane layer, the present invention uses distearoyl phosphatidylethanolamine-polyethylene glycol-lipoic acid (DSPE-PEG-LA) to modify the MoS2 membrane layer. There are some active sites on the surface of the molybdenum disulfide membrane layer. Under appropriate conditions, the lipoic acid end in DSPE-PEG-LA can interact with the active sites on the MoS2 surface to form a chemical bond, thereby achieving a firm combination of DSPE-PEG-LA and the molybdenum disulfide membrane layer. DSPE-PEG-LA is an amphiphilic molecule with a hydrophilic PEG chain and a lipophilic DSPE part. Exosomes are nanoscale vesicles with a typical phospholipid bilayer structure similar to that of cell membranes. The phospholipid end can spontaneously insert into the phospholipid bilayer of the exosome through hydrophobic interactions, thereby achieving binding with the exosome. After the phospholipid end is inserted into the phospholipid bilayer of the exosome, the PEG chain will form a physical barrier around it, reducing the nonspecific interaction between other substances and the phospholipid end, and enhancing the stability of the binding between the phospholipid end and the exosome. Changes in specific ion concentrations can achieve controlled release of exosomes. For example, adding calcium ions to the system can bind to the phosphate groups on the phospholipid molecules, changing the interaction between phospholipids and exosomes, thereby triggering the release of exosomes. In the phospholipid polyethylene glycol lipoic acid, polyethylene glycol is connected to the phospholipid end and the lipoic acid end respectively, the lipoic acid end is connected to the MoS2 membrane layer, and the phospholipid end is connected to the exosome. Not only can the exosomes be firmly loaded on the MoS2 membrane, but the release rate of the exosomes can be regulated by adjusting the changes in specific ion concentrations in the system, achieving regulation of the tissue growth process, and thus achieving an ideal effect of promoting bone bonding. MoS2 has antibacterial effects, and exosomes can promote the regeneration and repair of bone tissue. By adjusting the composition of the MoS2 membrane layer and the loading amount of the exosomes, the overall performance can be optimized. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0029] Figure 1are the surface morphologies of the metal implants in Example 1, Example 3, Example 6 and Example 11, wherein (a) is the surface morphology of the metal implant in Example 1, (b) is the surface morphology of the metal implant in Example 3, (c) is the surface morphology of the metal implant in Example 6, and (d) is the surface morphology of the metal implant in Example 11; Figure 2 are infrared spectra of the metal implants in Example 1, Example 3, Example 6 and Example 11, wherein (a) is the infrared spectrum of the metal implant in Example 1, (b) is the infrared spectrum of the metal implant in Example 3, (c) is the infrared spectrum of the metal implant in Example 6, and (d) is the infrared spectrum of the metal implant in Example 11; Figure 3 is the cell survival rate of the extract and MC3T3-E1 cells co-incubated for 72 hours, wherein (a) is the cell survival rate of the extract of Example 1, (b) is the cell survival rate of the extract of Example 3, and (c) is the cell survival rate of the extract of Example 11; Figure 4 The live / dead cell staining results of the extract and MC3T3-E1 cells co-incubated for 72 hours, wherein (a1) and (a2) are the staining results after incubation with the extract of Example 1, (b1) and (b2) are the staining results after incubation with the extract of Example 3, and (c1) and (c2) are the staining results after incubation with the extract of Example 11; Figure 5 are the results of the plate coating count test, wherein (a) is the result of the plate coating count test of Example 3, (b) is the result of the plate coating count test of Example 10, (c) is the result of the plate coating count test of Example 11, and (d) is the result of the plate coating count test of Example 12; Figure 6 are the results of the inhibition rate against Staphylococcus aureus, wherein (a) is the result of the inhibition rate against Staphylococcus aureus of Example 3, (b) is the result of the inhibition rate against Staphylococcus aureus of Example 10, (c) is the result of the inhibition rate against Staphylococcus aureus of Example 11, and (d) is the result of the inhibition rate against Staphylococcus aureus of Example 12; Figure 7 The color comparison diagram of blank control solution, sample solution and standard solution after adding Bradford G250 staining solution, where (a) is blank control solution, (b) and (c) are sample solutions with 1 / 100 and 3 / 100 volume of PBS solution added to calcium chloride solution, respectively, and (d) is 10 7 / mL of exosome solution. DETAILED DESCRIPTION
[0030] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0031] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0032] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0033] Example 1 The titanium alloy plate is cut into 8×8×2 mm pieces using wire cutting equipment. 3 The sample was cleaned and sandblasted, where the abrasive used was Al2O3, the abrasive size was 200 μm, the air flow velocity was 210 m / min, the nozzle distance was 15 cm, the gas pressure was 0.9 bar, and the sandblasting time was 30 s. After that, it was ultrasonically cleaned and dried with anhydrous ethanol and deionized water in turn, and then immersed in 10 mol / L hydrochloric acid and treated in an ultrasonic environment at 40 kHz and 26 ℃ for 30 min, and then cleaned with ultrapure water and dried for use.
[0034] Example 2 The titanium alloy after sandblasting and acid etching in Example 1 was placed in the inner tank of a hydrothermal reactor for use, 0.5 mmol of sodium molybdate dihydrate (Na2MoO4·2H2O) solid and 2 mmol of thioacetamide (CH3CSNH2) solid were weighed using an electronic balance, 50 mL of deionized water was added after mixing, and the mixed solution was added to the inner tank of the hydrothermal reactor containing the titanium alloy sample after sandblasting and acid etching after ultrasonic dissolution. The reactor was then sealed and placed in an oven at 200°C for reaction for 24 h. After the reaction was completed, the sample was cooled to room temperature and taken out. The sample was washed several times with ultrapure water under ultrasonic conditions and dried for use.
[0035] Example 3 The titanium alloy after sandblasting and acid etching in Example 1 was placed in the inner tank of a hydrothermal reactor for use. 1 mmol of sodium molybdate dihydrate (Na2MoO4·2H2O) solid and 4 mmol of thioacetamide (CH3CSNH2) solid were weighed using an electronic balance, 50 mL of deionized water was added after mixing, and the mixed solution was added to the inner tank of the hydrothermal reactor containing the titanium alloy sample after sandblasting and acid etching after ultrasonic dissolution. The reactor was then sealed and placed in an oven at 200°C for reaction for 24 h. After the reaction was completed, the sample was cooled to room temperature and taken out. The sample was washed several times with ultrapure water under ultrasonic conditions and dried for use.
[0036] Example 4 The titanium alloy after sandblasting and acid etching in Example 1 was placed in the inner tank of a hydrothermal reactor for use, 1.5 mmol of sodium molybdate dihydrate (Na2MoO4·2H2O) solid and 6 mmol of thioacetamide (CH3CSNH2) solid were weighed using an electronic balance, 50 mL of deionized water was added after mixing, and the mixed solution was added to the inner tank of the hydrothermal reactor containing the titanium alloy sample after sandblasting and acid etching after ultrasonic dissolution. The reactor was then sealed and placed in an oven at 200°C for reaction for 24 h. After the reaction was completed, the sample was cooled to room temperature and taken out. The sample was washed several times with ultrapure water under ultrasonic conditions and dried for use.
[0037] Example 5 3 mg of distearoylphosphatidylethanolamine-polyethylene glycol-lipoic acid (DSPE-PEG-LA) powder was dissolved in 10 mL of dichloromethane to obtain a DSPE-PEG-LA solution. 0.3 mL of 1 g / L nano-titanium dioxide dispersion was slowly added to the above solution, mixed evenly and placed in a reaction container, and the dried MoS2 film sample prepared in Example 2 was placed therein and illuminated for 12 h. The sample was then rinsed with distilled water 3 times and dried to obtain a phospholipid polyethylene glycol lipoic acid-modified MoS2 film.
[0038] Example 6 3 mg of distearoylphosphatidylethanolamine-polyethylene glycol-lipoic acid (DSPE-PEG-LA) powder was dissolved in 10 mL of dichloromethane to obtain a DSPE-PEG-LA solution. 0.3 mL of 1 g / L nano-titanium dioxide dispersion was slowly added to the above solution, mixed evenly and placed in a reaction container, and the dried MoS2 film sample prepared in Example 3 was placed therein and illuminated for 12 h. The sample was then rinsed with distilled water 3 times and dried to obtain a phospholipid polyethylene glycol lipoic acid-modified MoS2 film.
[0039] Example 7 3 mg of distearoylphosphatidylethanolamine-polyethylene glycol-lipoic acid (DSPE-PEG-LA) powder was dissolved in 10 mL of dichloromethane to obtain a DSPE-PEG-LA solution. 0.3 mL of 1 g / L nano-titanium dioxide dispersion was slowly added to the above solution, mixed evenly and placed in a reaction container, and the dried MoS2 film sample prepared in Example 4 was placed therein and illuminated for 12 h. The sample was then rinsed with distilled water 3 times and dried to obtain a phospholipid polyethylene glycol lipoic acid-modified MoS2 film.
[0040] Example 8 Take 30 μL 10 8 The exosome solution of human umbilical cord mesenchymal stem cells containing 100 g / mL was dripped onto the surface of the sample in Example 6, incubated in the dark at 4°C for 24 h, and dried at room temperature after ultrasonic cleaning to obtain a MoS2 film layer loaded with exosomes (antibacterial bone-promoting metal implant).
[0041] Example 9 Take 30 μL 10 9 The exosome solution of human umbilical cord mesenchymal stem cells was added dropwise to the surface of the sample in Example 6, incubated in the dark at 4°C for 24 h, and dried at room temperature after ultrasonic cleaning to obtain a MoS2 film layer loaded with exosomes (antibacterial bone-promoting metal implant).
[0042] Example 10 Take 30 μL 10 10 The exosome solution of human umbilical cord mesenchymal stem cells was added dropwise to the surface of the sample in Example 5, incubated in the dark at 4°C for 24 h, and dried at room temperature after ultrasonic cleaning to obtain a MoS2 film layer loaded with exosomes (antibacterial bone-promoting metal implant).
[0043] Embodiment 11 Take 30 μL 10 10 The exosome solution of human umbilical cord mesenchymal stem cells containing 100 g / mL was dripped onto the surface of the sample in Example 6, incubated in the dark at 4°C for 24 h, and dried at room temperature after ultrasonic cleaning to obtain a MoS2 film layer loaded with exosomes (antibacterial bone-promoting metal implant).
[0044] Example 12 Take 30 μL 10 10 The exosome solution of human umbilical cord mesenchymal stem cells / mL was added dropwise to the surface of the sample in Example 7, incubated in the dark at 4°C for 24 h, and dried at room temperature after ultrasonic cleaning to obtain a MoS2 film layer loaded with exosomes (antibacterial bone-promoting metal implant).
[0045] Figure 1The surface morphology of the metal implants in Example 1 (a), Example 3 (b), Example 6 (c) and Example 11 (d) is shown in FIG. Figure 1 It can be seen that after hydrothermal treatment, a nano-MoS2 film layer is formed on the surface of the titanium alloy after sandblasting and acid etching. After functionalization, the nanosheets become relatively dispersed and have clearer outlines. After loading exosomes, exosomes with a particle size between 85 and 150 nm and a clear membrane boundary structure were observed on the sample surface.
[0046] Figure 2 The infrared spectra of the metal implants in Example 1 (a), Example 3 (b), Example 6 (c) and Example 11 (d) are shown in FIG. 1 . Compared with the titanium alloy etched by sandblasting, the infrared spectra of the metal implants in Example 3 at 460 cm -1 、615 cm -1 The vibration peak of Mo-S appears near 555 cm -1 The characteristic peak of SS appears at 1100 cm -1 The vibration peak of CO, which is the characteristic peak of PEG, is significantly enhanced at 955 cm -1 The vibration of the PO bond of the phosphate group in DSPE-PEG-LA was observed near 1240 cm -1 and 1280 cm -1 The P=O bond vibration peak was observed near 1739 cm -1 The vibration peak of the carboxyl C=O in LA appears; the characteristic peak of molybdenum disulfide still exists, indicating that DSPE-PEG-LA has been successfully modified on the molybdenum disulfide membrane layer. After loading exosomes, the characteristic peaks of exosomes overlap with the characteristic peaks of molybdenum disulfide functionalized with DSPE-PEG-LA. The infrared absorption peaks of the exosome phospholipid bilayer membrane are reflected in the CH stretching vibration and P=O stretching vibration. It can be observed that after loading exosomes, the 2830 cm -1 , 2920 cm -1 The CH stretching vibration intensity increases at 1739 cm -1 The C=O vibration peak intensity at the 40°C increases, which may be due to the superposition of the C=O vibration peak of the exosome lipids. Combined with the surface morphology results, it can be shown that the exosomes are successfully loaded onto the molybdenum disulfide film layer.
[0047] Example 13 (1) CCK-8 assay to detect cell survival rate The sample of the embodiment is placed at 1.25 cm 2The extract was extracted at an extraction ratio of / mL in DMEM complete medium, 95% relative humidity, 5% CO2 and 37°C for 72 h to obtain the extract of the sample in the embodiment, which was filtered and sterilized for later use.
[0048] MC3T3-E1 cells were digested with 0.25% trypsin (containing EDTA) to prepare a single-cell suspension, centrifuged at 1000 rpm for 5 min, and resuspended in DMEM medium containing 10% fetal bovine serum to adjust the cell density to 3×10 4 The above cell suspension was inoculated into a 96-well plate, 0.2 mL per well, and a negative control and test group were set up, with 3 wells in each group, and cultured in a 37°C, 5% CO2 incubator for 24 h.
[0049] Take the 96-well culture plate inoculated and cultured for 24 h, aspirate the liquid in the well, add the extraction medium to the negative control group, add the extract of the sample of the example to the test group, 0.2 mL per well, and place it in a 5% CO2 incubator at 37 ℃ ± 2 ℃ for 72 h. Take the 96-well plate after 72 h of co-culture, aspirate the liquid in the well, wash each well once with phosphate buffer, add 10% CCK-8 culture medium at 0.1 mL / well, and continue to culture for 2 h under 5% CO2 and 37 ℃. Then use an ELISA instrument to detect and record the absorbance value of each well at a wavelength of 450 nm. Calculate the relative activity of each group of cells according to the formula.
[0050]
[0051] Among them, the background OD value is the absorbance of only adding CCK-8 reagent and culture medium; the blank group OD value is the absorbance of the blank control group; the test group OD value is the absorbance of the test group.
[0052] The results are as follows Figure 3 As shown, compared with the titanium alloy and MoS2 film layers treated with sandblasting and acid etching, the MoS2 film layers loaded with exosomes showed a higher cell survival rate, indicating that the MoS2 film layers loaded with exosomes have obvious advantages in terms of cell compatibility.
[0053] (2) Live / dead cell staining experiment The sample of the embodiment is placed at 1.25 cm 2 The extract was extracted at an extraction ratio of / mL in DMEM complete medium, 95% relative humidity, 5% CO2 and 37°C for 72 h to obtain the extract of the sample in the embodiment, which was filtered and sterilized for later use.
[0054] Digest MC3T3-E with 0.25% trypsin (containing EDTA) 1Single cell suspension was prepared by centrifuging at 1000 rpm for 5 min, and the cells were resuspended in DMEM medium containing 10% fetal bovine serum to adjust the cell density to 4 × 10 4 / mL. The above cell suspension was inoculated into a 24-well plate, 1 mL was inoculated into each well, and negative control and test groups were set up, and the plates were placed in a 37 ℃, 5% CO2 incubator for 24 h. Take the 24-well culture plate that was inoculated and cultured for 24 h, aspirate the liquid in the well, add the extraction medium to the negative control group, add the sample extraction solution of the test group, 1 mL per well, and place it in a 5% CO2 incubator at 37 ℃±2 ℃ for 72 h. Take the 24-well culture plate that was inoculated and cultured for 24 h, aspirate the liquid in the well, add the extraction medium to the negative control group, add the sample extract of the test group, 1 mL per well, and place it in a 5% CO2 incubator at 37 ℃±2 ℃ for 72 h.
[0055] Use dye diluent (solution C) to dilute reagent A (Calcein-AM) and reagent B (PI) 10 times respectively; take 985.5 μL serum-free medium and mix with 10 μL diluted reagent A and 4.5 μL reagent B to obtain the dye working solution, which is ready for use. Take the 24-well plate after 72 hours of co-culture, aspirate the liquid in the well, and wash each well once with phosphate buffer. Add 1 mL of the dye working solution to each well, incubate at 4℃ in the dark for 15 minutes, and observe with a fluorescence microscope. The results are as follows: Figure 4 As shown, the MC3T3-E1 cells in the MoS2 film layer loaded with exosomes not only had a more complete morphology, but also had a significantly improved survival rate.
[0056] (3) Antibacterial experiment LB liquid culture medium: Use a measuring cylinder to measure 100 mL of distilled water and pour it into a 250 mL reagent bottle. Use an analytical electronic balance to weigh 2.5 g of LB broth culture medium and add it to mix well. Sterilize it in a high-temperature and high-pressure steam sterilizer at 121 ℃ for 15 min and set aside for use.
[0057] LB solid medium: Use a measuring cylinder to measure 100 mL of distilled water and pour it into a 250 mL reagent bottle. Use an analytical electronic balance to weigh 2.5 g of LB broth medium and 1.5 g of agar powder. Add the above weighed reagents and mix well. Sterilize in a high-temperature and high-pressure steam sterilizer at 121°C for 15 minutes. When the medium cools to about 40-50°C, use an electric pipette to draw 15 mL of the medium and pour it into a disposable sterile plate.
[0058] Take two 12 mL bacterial culture tubes, add 3 mL LB liquid culture medium to each, pick a single colony from the solid culture medium of Staphylococcus aureus and add it to the liquid culture medium, and use the other tube as a blank control. Place in a constant temperature shaker (37 ℃, 200 rpm) and shake culture overnight (15 h).
[0059] The samples of the embodiment were placed in 12 mL bacterial culture tubes according to the groups for later use.
[0060] Dilute the bacterial solution to 10 with sterile PBS solution. 6 CFU / mL, based on the total surface area of the sample and the volume of the added bacterial solution 2.2 cm 2 / mL, add the diluted bacterial solution to the bacterial culture tube containing the sample of the embodiment. The control group is a group without adding sample. Place it in a 3 ℃ constant temperature incubator and culture it for 24 hours.
[0061] After the culture is completed, the bacterial solution is diluted 10 times with sterile PBS solution, and 100 μL of the dilution is evenly spread on the LB solid medium. Place it in a 37°C constant temperature incubator for 18 hours, take it out, take pictures and record the number of colonies.
[0062] The calculation method of bacterial solution concentration (CFU / mL) is: colony count × dilution factor × 10 (0.1 mL coating); Antibacterial rate = (1-concentration of bacterial solution in experimental group / concentration of bacterial solution in control group) × 100%; The results are as follows Figure 5 and 6 As described above, the results showed that after culturing for 24 hours at 37 °C, the MoS2 film layer loaded with exosomes had a good inhibitory effect on Staphylococcus aureus. When the concentration of the MoS2 film layer was low, its inhibitory effect on Staphylococcus aureus was not obvious. However, as the concentration of MoS2 in the film layer increased, the inhibitory effect of the sample on Staphylococcus aureus gradually increased. Compared with the MoS2 film layer, the MoS2 film layer loaded with exosomes showed a higher inhibition rate.
[0063] Embodiment 14 Take two samples of Example 10 and place them in reaction vessels respectively. According to the ratio of sample surface area to PBS solution volume of 1.25 cm 2 / mL ratio, add PBS solution to each container. Then, add 2 mmol / L calcium chloride solution with a volume of 1 / 100 and 3 / 100 of the PBS solution to the container in turn, and shake gently. After 6 hours of reaction, take 1.0 mL of solution from each container as the sample solution. At the same time, prepare an equal volume of PBS buffer as a blank solution and an equal volume of PBS buffer prepared with a concentration of 10 7 / mL exosome solution was used as the standard solution. Then, 1.0 mL of Bradford G250 staining solution was added to the blank solution, sample solution and standard solution respectively. After thorough mixing, the solution was incubated at room temperature for 10 minutes to observe the color change of the solution. The staining solution will form a blue compound after combining with protein. Since exosomes contain protein, the solution with a low exosome content has a correspondingly low protein content, and the blue color presented after reacting with the staining solution is relatively lighter; while the solution with a high exosome content has a high protein content, and the blue color presented after combining with the staining solution is also darker.
[0064] Figure 7 From left to right are the blank control solution, the sample solution with 1 / 100 and 3 / 100 of the PBS solution volume added, and the sample solution with a concentration of 10 7 / mL exosome solution. Through direct colorimetric analysis, it can be visually observed that the solution in each test tube presents a different color. The blank control solution test tube presents the original color of the dye solution, 10 7 The blue color of the standard solution of exosomes / mL is the deepest. In the sample system of Example 10, the blue color in the sample solution test tube with a large amount of calcium chloride added deepens. This is because calcium ions can bind to the phosphate groups on the phospholipid molecules, changing the original interaction between phospholipids and exosomes, thereby promoting the release of exosomes. Based on the above comparative analysis, it can be seen that by adjusting the calcium ion concentration in the system, the controllable release of exosomes can be achieved.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An antibacterial bone-promoting metal implant, characterized in that: The method uses a metal implant as a matrix, the surface of the matrix is loaded with a MoS2 film, and the MoS2 film is modified with exosomes.
2. The antibacterial bone-promoting metal implant according to claim 1, characterized in that: The metal implant comprises a titanium-based implant.
3. The antibacterial bone-promoting metal implant according to claim 1, characterized in that: The exosome sources include cells and / or body fluids; Wherein, the cells include at least one of stem cells, macrophages, endothelial cells and epithelial cells of humans, rats or mice.
4. The method for preparing the antibacterial bone-promoting metal implant according to any one of claims 1 to 3, characterized in that: The steps include: (1) Roughening the surface of the metal implant; (2) dissolving sodium molybdate and thioacetamide in water to obtain a mixed solution, immersing the roughened metal implant in the mixed solution to carry out a hydrothermal reaction, and obtaining a metal implant with a surface-loaded MoS2 film after the reaction is completed; (3) immersing the metal implant with the MoS2 film loaded on the surface into a distearoylphosphatidylethanolamine-polyethylene glycol-lipoic acid solution containing dispersant nano-titanium dioxide, and irradiating with light to obtain a phospholipid polyethylene glycol-lipoic acid-modified MoS2 film; (4) Add the exosome solution dropwise onto the surface of the metal implant in step (3), and after incubation, obtain an antibacterial bone-promoting metal implant.
5. The preparation method according to claim 4, characterized in that: In step (1), the roughening treatment includes sandblasting and acid etching; During the sandblasting and acid etching treatment, the abrasive particles used include Al2O3; During the sandblasting and acid etching treatment, the size of the abrasive particles used is 150-250 μm; During the sandblasting and acid etching treatment, the air flow velocity is 200-220 m / min; the nozzle distance is 14-18 cm; the gas pressure is 0.8-1.0 bar; and the sandblasting time is 25-35 s; During the sandblasting and acid etching treatment, the acid etching solution used is a hydrochloric acid solution.
6. The preparation method according to claim 4, characterized in that: In step (2), the temperature of the hydrothermal reaction is 180-220° C.; the time of the hydrothermal reaction is 12-48 h; The molar ratio of sodium molybdate and thioacetamide is (0.8~1.2):(3.5~5); The concentration of sodium molybdate in water is 2~30 mM.
7. The preparation method according to claim 4, characterized in that: In step (3), the concentration of the distearoylphosphatidylethanolamine-polyethylene glycol-lipoic acid solution is 0.2-1 g / L; Or, the mass ratio of nano-titanium dioxide to distearoyl phosphatidylethanolamine-polyethylene glycol-lipoic acid is 1:1-1:20; The concentration of nano-titanium dioxide is 0.8~1.2 g / L; The light reaction time is 8~24 h.
8. The preparation method according to claim 4, characterized in that: In step (4), the amount of exosomes added was 28-35 μL; the concentration of the exosome solution was 10 7 ~10 11 Pieces / mL.
9. The preparation method according to claim 4, characterized in that: In step (4), the incubation is carried out in a dark environment at a temperature of 3 to 5°C and a time of 12 to 36 hours.
10. Use of the antibacterial bone-promoting metal implant according to any one of claims 1 to 3 in the preparation of orthopedic and / or dental metal implants.
Citation Information
Patent Citations
Exosome-loaded metal-based implant material as well as preparation method and application thereof
CN111701076A
Titanium dioxide nanotube / molybdenum disulfide nanoflower compound as well as preparation method and application thereof
CN113244393A
Preparation method of active contact type antibacterial coating on titanium alloy surface
CN118147620A
Post box establishment system using telecommunication network of apartment houses
KR102274858B1